Undercurrents : queer culture and postcolonial Hong Kong - Leung, Helen Hok-Sze, 1967- (Sexuality studies series., 2008)
"Undercurrents engages the critical rubric of "queer" to examine Hong Kong's screen and media culture during the transitional and immediate postcolonial period. Helen Hok-Sze Leung draws on theoretical insights from a range of disciplines to reveal parallels between the crisis and uncertainty of the territory's postcolonial transition and the queer aspects of its cultural productions." "Leung explores Hong Kong cultural productions - cinema, fiction, popular music and subcultural projects - and argues that while there is no overt consolidation of gay and lesbian identities in Hong Kong culture, undercurrents of diverse and complex expressions of gender and sexual variance are widely in evidence." "Undercurrents uncovers a queer media culture that has been largely overlooked by critics in the West, and demonstrates the cultural vitality of Hong Kong amidst political transition. It will appeal to scholars and general readers interested in Asian studies, film and cultural studies, and sexuality and gender studies."--Jacket